the Challenges and opportunities: application of clean and affordable energy in the development of the national capital of the archipelago - Dodi Al Vayed; Eko Priyo Purnomo (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2023)
IKN is in a good and sufficient position in terms of energy security, especially in terms of renewable energy. To prevent harm to Kalimantan's ecology and natural beauty, it is vital to pay attention to and routinely checkfactors of energy efficiency and emission levels. This research aimed to look at the challenges and opportunities of implementing clean and affordable energy in the development of the National Capital of the Archipelago. This study used qualitative research methods that described the findings throughonline media, and the data source of this research is online news media. The data was obtained using the Ncapture feature on the Nvivo 12 Plus. The results of the study showed that the development of the Kayan River Hydroelectric Power Plant encourages economic development by as much as 37%, environmental development by as much as 35%, and social development by as much as 28%. Then the second challenge of hydropower development is environmental development, as much as 33.33%. The third challenge is economic development, which is 31.82%. Kayan hydropower construction will consist of five dams, the first phase will produce a 900-megawatt dam, the second dam of 1,200 megawatts, the third dam of 1,800 megawatts, the fourth dam of 1,800, and the fifth dam of 3,200 megawatts.